PENERAPAN ALAT PENIRIS ABON LELE SISTIM SENTRIFUGAL DENGAN PENGATUR WAKTU DAN PUTARAN PADA INDUSTRI KECIL RUMAH TANGGA - Riana, Ayik (Program Kreativitas Mahasiswa - Teknologi, 2013)
Boyolali the county as well as agricultural areas are also a lot of people who are self-employed in the field of fisheries. One of the villages in the district of Palm Boyolali Tegalrejo is precisely in the village is the center of catfish farmers or village is often referred to as the catfish, because this area irrigation system is easy, but the land is not so fertile. in addition many are also many who cultivate farming/livestock catfish, tilapia fish and nag. At one point sometimes abundant fish harvest/surplus, then comes the idea of a housewife, how dishes of fish not only cooked and eaten (fried, baked) then made other kinds of fish dishes that made shredded. Besides durable was no less prestige with shredded cow. This iterative refinement turns made while held good and prospected. Even until the laboratory tests conducted on non cholesterol UGM turns, making it suitable for toddlers, seniors and people who prioritize health in general. In order to accommodate the harvest of fish farmers/fish farmers so established SMEs. The SME SME named MAMI (dharma mina) is located in the village Tegalrejo. The main problem faced by the SMEs is the supporting equipment production process. The equipment is the dominant fryer, presses (drainer) and oven. The desire of SMEs will increase its production capacity, however there is the most urgent problem is the tool presses (drainer) after completion of the oil pan. Equipment presses (drainer) is still very manual is the model of the lever. By looking at the condition of the course, SMEs need assistance and a touch of technology to speed up the production process. Program for Appropriate Technology development will result in a tool that serves to relieve the burden on small industries in order to increase revenue and productivity as well as a discourse for small industries, that this tool can be used for other waste treatment especially fibrous. In general, the economic potential of the products obtained, among others: the cost of making cheap instruments, oil draining process can be completed. Viewed from the side of science and technology, there are two value-added utilization of appropriate technology, and use of Tilapia and fish dishes nag as an alternative, which is a shredded. The design tool is simple, but has a very high benefit. The methodology used in the field survey, determine the capacity of the machine, machine design, manufacture, testing machines, evaluation. From the results of this engineering tool, it can be concluded as follows: (1) Equipment shredded oil drainer result of this design can work well, as expected. (2) Equipment drainer shredded fish small industry is very helpful in the process of making the shredded fish as an alternative side dish.